United by Hope, Divided by Access: Country Mapping of COVID-19 Information Accessibility and Its Consequences on Pandemic Eradication - Dror, Amiel A.; Morozov, Nicole G.; Layous, Eli; Mizrachi, Matti; Daoud, Amani; Eisenbach, Netanel; Rayan, Doaa; Kaykov, Edward; Marei, Hesham; Barhum, Masad; Srouji, Samer; Avraham, Karen B.; et al. (Frontiers in Medicine, 2021)
Many government websites and mobile content are inaccessible for people with vision, hearing, and cognitive disabilities. The COVID-19 pandemic highlighted these disparities when health authority website information, critical in providing resources for curbing the spread of the virus, remained inaccessible for numerous disabled populations. The Web Content Accessibility Guidelines provide comparatively universally accepted guidelines for website accessibility. We utilized these parameters to examine the number of countries with or without accessible health authority websites. The resulting data indicate a dearth of countries with websites accessible for persons with disabilities. Methods of information dissemination must take into consideration individuals with disabilities, particularly in times of global health crises.